An optimal window for the fabrication of Edible Polyelectrolyte Complex Nanotubes (EPCNs) from bovine serum albumin (BSA) and sodium alginate. (April 2018) - Maldonado, L.; Kokini, J.
Abstract: Edible polyelectrolyte complex nanotubes (EPCNs) were assembled with the alternate layer-by-layer (LbL) deposition technique using bovine serum albumin (BSA) as positively charged biopolymer and sodium alginate as negatively charged biopolymers. The specific manufacturing conditions that led to the formation of defined and stable nanotubular structures were studied. Dynamic light scattering (DLS) and isothermal titration calorimetry (ITC) were used to study the ability of a protein and polysaccharide to interact and form nanotubes. These methods also offer insights into the types of interactions occurring between these two biopolymers. ITC measurements indicated that electrostatic interactions between BSA and sodium alginate were predominant at pH 3–4, while a strong electrostatic repulsion occurred at pH 6–7. This was also correlated by zeta potential measurements that showed opposite charges for these two biopolymers at acidic pH and similar charges at neutral pH. The ability of a protein and polysaccharides to interact and form nanotubes were studied with the assistance of polycarbonate (PC) templates (pore diameters: 200, 400, 600 and 800 nm). Other assembly parameters, including ratio and concentration of biopolymers, rates of addition, and stability at different pH values were also studied. It was possible to form stable EPCNs with diameters of 200, 400, 600 and 800 nm-template. The wall thickness that leads to the most stable EPCN is 4 bilayers [(BSA/ALG)4 ] with a rate of addition of 1.0 ml/min and biopolymers concentrations of 0.8 mg/ml and 0.6 mg/ml for BSA and alginate, respectively. The morphology, outer diameter, thickness of the wall and length of the freeze dried EPCNs were characterized with SEM. The SEM images showed that (BSA/ALG)1 and (BSA/ALG)2 yield a weaker EPCN whereas (BSA/ALG)3 yields a more robust wall thickness. Graphical abstract: Image 1 Highlights: Edible nanotubes can be fabricated from BSA and sodium alginate at pH 3–4. The layer by layer deposition technique is used with the assistance of a template. Flow rate and residence time need to be optimized for successful fabrication. We discovered a delicate stoichiometric concentration ratio of the polyelectrolytes.